2019
DOI: 10.1017/s2045796019000623
|View full text |Cite
|
Sign up to set email alerts
|

Air pollutants and daily number of admissions to psychiatric emergency services: evidence for detrimental mental health effects of ozone

Abstract: Aims Aim of the current study is to investigate the associations between daily levels of air pollutants (particulate matter, ozone, carbon monoxide, nitrogen dioxide) and daily admissions for mental disorders to the emergency department of two general hospitals in Umbria region (Italy). Methods We collected data about daily admissions to psychiatric emergency services of two general hospitals, air pollutants' levels and meteorological data for the time period 1 January 2015 until 31 Dece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 35 publications
(59 reference statements)
0
21
1
Order By: Relevance
“…Similarly, Xue et al (2020) studied spatiotemporal variations for Shanghai and suggested that increased focus on urban residential planning and introduction of emission management policies have significantly reduced NO 2 concentrations in Shanghai. Bernardini et al (2020) explored the impact of air pollutants, i.e., O 3 , and suggested that a number of patients into the emergency section have direct correlation with air pollutants. Furthermore, Adach et al (2020) and Ha (2020) registered similar findings.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Xue et al (2020) studied spatiotemporal variations for Shanghai and suggested that increased focus on urban residential planning and introduction of emission management policies have significantly reduced NO 2 concentrations in Shanghai. Bernardini et al (2020) explored the impact of air pollutants, i.e., O 3 , and suggested that a number of patients into the emergency section have direct correlation with air pollutants. Furthermore, Adach et al (2020) and Ha (2020) registered similar findings.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers and healthcare practitioners across fields of biomedicine acknowledge the tremendous impact that environmental exposures have on health and disease. For example, airborne pollutant exposures have been linked to diseases as diverse as asthma [1][2][3][4][5][6], diabetes [7][8][9], cardiovascular disease [10], dementia [11], mental health disorders [12], obesity [13], liver disease [14], and premature mortality [15]. Yet, informatics tools to study the interaction between environmental exposures and health outcomes at the level of the individual are largely non-existent.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers and healthcare practitioners across fields of biomedicine acknowledge the tremendous impact that environmental exposures have on health and disease. For example, airborne pollutant exposures have been linked to diseases as diverse as asthma [1][2][3][4][5][6], diabetes [7][8][9], cardiovascular disease [10], dementia [11], mental health disorders [12], obesity [13], liver disease [14], and premature mortality [15]. Yet, informatics tools to study the interaction between environmental exposures and health outcomes at the level of the individual are largely non-existent.…”
Section: Introductionmentioning
confidence: 99%